1978
DOI: 10.1055/s-0028-1093412
|View full text |Cite
|
Sign up to set email alerts
|

Non-Glucoregulatory Hormones (T4, T3, rT3, TSH, Testosterone) during Physical Exercise in Juvenile-Type Diabetics

Abstract: Non-glucoregulatory hormones (T4, T3, rT3, TSH and testosterone) were studied by radioimmunoassay in juvenile-type diabetics in moderate control and in ketosis due to insulin withdrawal and in age matched "normals" during a mild prolonged exercise test. The basal serum hormone levels revealed the following findings: Serum testosterone was markedly lower in diabetics than in normals ( 177 +/- 24 resp. 618 +/- 52 ng/dl). This is in contrast to other studies, but it may reflect decreased testicular function due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 3 publications
(3 reference statements)
3
18
1
3
Order By: Relevance
“…In other words, there are contradictions about the cause and effect of physical exercise and the amount of testosterone in different researches [7,16,[20][21][22]. Besides the studies reporting that free and total testosterone levels did not change with exercise [23][24][25], there are also those noting that free and total testosterone levels significantly decreased with exercise [26][27][28]. The increase we obtained in free and total testosterone levels immediately after exhaustion is in contrast with the findings of these researchers.…”
Section: Discussionmentioning
confidence: 96%
“…In other words, there are contradictions about the cause and effect of physical exercise and the amount of testosterone in different researches [7,16,[20][21][22]. Besides the studies reporting that free and total testosterone levels did not change with exercise [23][24][25], there are also those noting that free and total testosterone levels significantly decreased with exercise [26][27][28]. The increase we obtained in free and total testosterone levels immediately after exhaustion is in contrast with the findings of these researchers.…”
Section: Discussionmentioning
confidence: 96%
“…Berchtold et al [30] reported that during very prolonged submaximal exercise ( ∼ 3 h), total T 4 remained constant but then declined significantly during recovery. In the same study, the level of T 3 continuously declined during exercise.…”
Section: Exercise Effectsmentioning
confidence: 97%
“…The discrepancy in these findings may be related to the fact that these studies failed to completely account for the influence of nutrient balance on the thyroid turnover rate, i.e. a negative energy balance has been shown to substantially reduce the thyroid responses [23,[30][31][32][33][34][35][36][37][38][39] . However, Baylor and Hackney [35] followed elite athletes during a 20-week training competition cycle and found that resting free T 3 and TSH were reduced during intensive competitive periods even though no significant changes in body mass occurred.…”
Section: Exercise Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…1976;Dessypris et al, 1976;Kuoppasalmi et al, 1976;Brisson et al, 1977Brisson et al, , 1979Galbo et al, 1977;Berchtold et al, 1978]. For prolactin (PRL), reports are almost nonexistent.…”
Section: Introductionmentioning
confidence: 99%